It's a Man's World, Try to Convince the Men Otherwise: The Role of Women in Irish Policing. Issue 3 (4th May 2019) - Marsh, Courtney
Abstract : Police organizations are historically and predominantly male organizations; as such, the purpose of this study is to examine the role of women in Irish policing. The literature review will analyze gender-specific organizational literature, focused on the United States. Theoretical components include biological determination and social constructivism in the policing context. The study is conducted through qualitative interviews and thematic analysis of 10 current and former Gardaí in Ireland. This study empirically contributes to how the organization views gender and how those differences are institutionalized in that Gardaí are treated differently based on their gender.